Taxonomic treatment of the Ficus auriculata complex (Moraceae) and typification of some related names - Zhang, Zhen; Wang, Xiao-Mei; Liao, Shuai; Tian, Huai-Zhen; Li, Hong-Qing (Phytotaxa, 2019)
Typification of Ficus auriculata complex (Ficus subsect. Neomorphe) is discussed and F. beipeiensis is treated as a new synonym of F. auriculata. As the original material of F. auriculata has not been located, a presentative specimen deposited at P is designated here as its neotype after detailed study of the protologue, relevant publications and specimens.